Kinship across the black Atlantic : writing diasporic relations. - ADAIR, GIGI (Postcolonialism across the disciplines ;, 2019)
This book combines insights from postcolonial, queer and diaspora studies to consider the meanings of kinship in contemporary black Atlantic fiction. Diasporic displacement generates new understandings and new narratives of kinship. An analysis of kinship is thus essential to understanding diasporic modernity at the turn of the twenty-first century.